Glymphatic System Dysfunction in Elderly Patients with Late-Onset Epilepsy and Comorbid Chronic Insomnia Revealed by Diffusion Tensor Imaging Along the Perivascular Space (DTI-ALPS) - Wang Y; Hu J; Zhang YY; Wang FY; Wu JC; Wang L (Neuropsychiatric Disease and Treatment)
Yu Wang,1,2,* Jie Hu,2,3,* Yue-Yu Zhang,2,3 Fu-Yu Wang,4 Jun-Cang Wu,2 Long Wang2 1Graduate School of Wan Nan Medical College, Wuhu, Anhui, 241002, People’s Republic of China; 2Department of Neurology, The Second People’s Hospital of Hefei, Hefei, Anhui, 230011, People’s Republic of China; 3The Fifth Clinical Medical College of Anhui Medical University, Hefei, Anhui, 230032, People’s Republic of China; 4Department of Pharmacy, The Second People’s Hospital of Hefei, Hefei, Anhui, 230011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Long Wang, Department of Neurology, The Second People’s Hospital of Hefei, Hefei, Anhui, 230011, People’s Republic of China, Email guxindao606@126.comPurpose: This study assessed the influence of glymphatic system (GS) dysfunction on cognitive decline in patients with late-onset epilepsy (LOE) and comorbid chronic insomnia utilizing diffusion tensor imaging along the perivascular space (DTI-ALPS).Methods: Clinical data were collected from 42 elderly LOE patients, 17 with and 25 without chronic insomnia, as well as from 22 healthy controls (HCs) matched for age and sex. Simoa assays were performed to quantify Aβ 42 and Aβ 40 as plasma biomarkers of age-related neuropathology, and associations between the DTI-ALPS index and age, seizure frequency and duration, Sleep Quality Index (PSQI), Hamilton Rating Scale for Depression (HAMD), Hamilton Rating Scale for Anxiety (HAMA), Mini-Mental State Examination (MMSE), and Aβ 42:Aβ 40 ratio (Aβ 42/40) were assessed using Spearman correlation tests and multivariate logistic regression models.Results: Both DTI-ALPS index and Aβ 42/40 were significantly lower among LOE patients compared to HCs, and post-hoc analysis revealed even lower Aβ 42/40 and DTI-ALPS index values among LOE patients with comorbid chronic insomnia compared to HCs and LOE patients without chronic insomnia. The DTI-ALPS index was negatively correlated with age, disease duration, PSQI score, and HAMA score, and positively correlated with Aβ 42/40 and MMSE score among LOE patients according to Spearman’s tests. Multivariate linear regression revealed independent associations of the DTI-ALPS index with age, MMSE score, Aβ 42/40, and PSQI after adjusting for vascular risk factors, sex, and education.Conclusion: These results suggest that the GS is dysfunctional in LOE and may exacerbate sleep disruption and cognitive impairments.Keywords: glymphatic system, late-onset epilepsy, chronic insomnia, cognitive function, DTI-ALPS